An Evaluation of Serum IgE and Th2-Associated Interleukins in Children With Uncomplicated and Complicated Appendicitis - Gudjonsdottir, Johanna; Roth, Bodil; Lovén, Gustav; Ohlsson, Bodil; Hagander, Lars; Salö, Martin (Frontiers in Pediatrics, 2022)
Background The pathogenesis of appendicitis is not understood completely and establishing a correct diagnosis can be clinically challenging. Previous investigations have shown an association between a T helper cell (Th)2-mediated inflammatory response, for example immunoglobulin E (IgE)-mediated allergy, and a decreased risk of complicated appendicitis. The present study aimed to evaluate differences in serum concentrations of IgE and Th2-associated interleukins (IL) in children with uncomplicated and complicated appendicitis. Method A prospective study including children <15 years with appendicitis. Blood samples were collected preoperatively at the time of clinical assessment at the Pediatric Emergency Department and analyzed for concentrations of serum total IgE and IL-4, IL-9, and IL-13. Associations with complicated appendicitis were evaluated through logistic regression adjusting for age, appendicolith, and symptom duration. Results 138 children with confirmed appendicitis were included. The median age was 10 (IQR 8-12) years, 87 (63%) were boys and 58 (42%) had complicated appendicitis. Children with complicated appendicitis had significantly higher concentrations of IL-9 and IL-13 compared to children with uncomplicated appendicitis. In the univariate logistic regression, high concentrations of IL-13 were associated with an increased risk of complicated appendicitis (OR 1.02 (95% CI 1.01-1.04) p=0.005), which remained in the multivariate analysis (aOR 1.02 (95% CI1.01-1.04), p=0.01). Serum concentrations of IgE, IL-4, and IL-9 did not significantly affect the risk of complicated appendicitis. Conclusion High levels of IL-13 seem to be associated with an increased risk of complicated appendicitis. This is incongruent with the hypothesis of an Th1/Th17-driven inflammation in this type of appendicitis.